The Real Product Market Impact of Mergers - SHEEN, ALBERT (Journal of Finance, 2014)
ABSTRACT I document sources of value creation in mergers by analyzing novel data on the quality and price of goods sold by merging firms. When two competitors in a product market merge, their products converge in quality, and prices fall relative to the competition. These effects take two to three years to be fully realized and are stronger in mature industries. Prices do not fall, however, when the acquirer is diversifying into a new product market. This direct evidence of real changes induced by merger activity is consistent with consolidation by related merging firms to achieve operational efficiencies and lower costs.